Estudo da reação de produção de ésteres de ácidos graxos por via enzimática objetivando aplicações alimentícias - Sampaio Neta, Nair do Amaral (2007)
Several experiments were done aiming at the study on the enzymatic esterification of the oleic acid with fructose in ethanolic medium, focusing the synthesis of biodegradable biosurfactants. For that purpose, it was utilized the enzyme, Candida antartica B., at temperature of 55 ºC, in reacting time of 48, 72, 96 e 120 hours. Accordingly to the obtained results it was verified that the related enzyme catalyzed primarily the ethanol present in the reactional medium to form the ester: ethyl oleate. This fact was confirmed through magnetic nuclear resonance spectra (1H and 13C) as well as, through infrared spectrum, by the presence of absorption peak at 1738, 4 cm- 1, characteristic of that ester. The results of the reaction of ethyl oleate production indicate that the highest yield was observed in about 96 hours time, and for the 120 hours time it was observed also an inferior yield. The experiments accomplished for the obtention of fructose esters from oleic acids in ethanolic medium were not successful like in other solvents not recommended for food use. The ethyl oleate shows a lipophilic character and in the food industry it finds application in the osmotic dehydration of tomatoes and peppers “dedo de moça”, improving water release, sugar yield and solar brightness. The use of ethyl oleate in the dehydration process decreases the drying time increases its efficiency without leaving any traces pf chemical residues